In view of standardization: Comparison and analysis of initial management of severely burned patients in Germany, Austria and Switzerland. Issue 1 (February 2015) - Münzberg, Matthias; Ziegler, Benjamin; Fischer, Sebastian; Wölfl, Christoph Georg; Grützner, Paul Alfred; Kremer, Thomas; Kneser, Ulrich; Hirche, Christoph
Highlights Twenty-one level one burn centers in Germany, Austria and Switzerland were surveyed. Organization and management of burn trauma admissions were evaluated. Most burn centers use an individual standard operating procedure for admission. There is a lack of standardization in burn centers across German speaking countries. Standardized guidelines for burn care have to be developed to improve quality of care.